Cancer in the Spine Comprehensive Care - McLain, Robert F.; McLain, Robert F.; Markman, Maurie.; Markman, Maurie.; Bukowski, Ronald M.; Bukowski, Ronald M.; Macklis, Roger.; Macklis, Roger.; Benzel, Edward C.; Benzel, Edward C. (Current Clinical Oncology, 2006)
Cancer involving the spinal column presents a serious clinical challenge. Properly selected and delivered treatment strategies can insure dramatically better survival and quality of life than ever attainable in the past. Improved therapies and a multidisciplinary approach to patient care now make it possible to treat even the most ominous tumors of the spine with a higher likelihood of success. In Cancer in the Spine: Comprehensive Care, distinguished physicians and researchers from prestigious cancer centers around the world critically examine current trends and innovations in spinal cancer management. Detailing both the fundamental principles of diagnosis and treatment planning, and the cutting-edge techniques of tumor treatment, these experts bring together in one volume a guide to coordinated management of all aspects of cancer in the spine. This comprehensive overview of current and investigational therapies covers chemo- and radiation therapy, pain management, diagnostic radiology, as well as reconstructive surgery and palliative care. Highlights include management of vertebral metastases, minimally invasive surgery for spinal lesions, innovations in radiotherapy, treatment of pathological fractures, and management strategies for primary malignancies, as well as guides to long-term follow-up and end-of-life care. Whether managing the initial evaluation and diagnosis, or providing terminal care for the critically ill, physicians of all backgrounds will find Cancer in the Spine: Comprehensive Care an invaluable reference, providing a wealth of authoritative, multidisciplinary information essential to delivery of optimal treatment to these challenging and deserving patients.